2014
DOI: 10.1080/02626667.2014.923969
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of the hydrological response of the Gaping River basin to radar-raingauge quantitative precipitation estimates

Abstract: The generation of reliable quantitative precipitation estimations (QPEs) through use of raingauge and radar data is an important issue. This study investigates the impacts of radar QPEs with different densities of raingauge networks on rainfall-runoff processes through a semi-distributed parallel-type linear reservoir rainfall-runoff model. The spatial variation structures of the radar QPE, raingauge QPE and radar-gauge residuals are examined to review the current raingauge network, and a compact raingauge net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that radar QPE can be a useful and reliable forcing for flood/streamflow forecasting in poorly gauged or ungauged regions [61,65]. For gauged areas, radar precipitation can be merged with gauged precipitation to generate a more accurate QPE product with a good spatiotemporal coverage and resolution, so as to benefit rainfall-runoff modelling and flood simulation [61,[67][68][69][70][71].…”
Section: Implementation Of Weather Radar Precipitationmentioning
confidence: 99%
“…It has been demonstrated that radar QPE can be a useful and reliable forcing for flood/streamflow forecasting in poorly gauged or ungauged regions [61,65]. For gauged areas, radar precipitation can be merged with gauged precipitation to generate a more accurate QPE product with a good spatiotemporal coverage and resolution, so as to benefit rainfall-runoff modelling and flood simulation [61,[67][68][69][70][71].…”
Section: Implementation Of Weather Radar Precipitationmentioning
confidence: 99%
“…Further research requires further acquisitions of sub-daily discharges with high temporal resolution to en-able more accurate flood warning modeling. Meanwhile, it has also been indicated that the spatial characteristics of rainfall could significantly affect the flooding process and further enhance the model results based on finer spatial resolution of radar precipitation data [49].…”
Section: The 24 H Critical Areal Rainfall Thresholds For Early Flood ...mentioning
confidence: 99%
“…The first two papers (Harrison et al 2014, Yeung et al 2014 concern radar-rainfall estimation and quality control, while uncertainty aspects of radar-rainfall estimation, including reduction through merging with raingauge data, are covered by Delrieu et al (2014), Seo et al (2014) and Pan et al (2014). Morin and Yakir (2014) and Nikolopoulos et al (2014) exploit radar rainfall to gain a deeper understanding of the impact of spatial rainfall on catchment flood response, including consideration of localized convective rain in semi-arid environments and the interplay of storm velocity and orography on flood magnitude.…”
Section: Weather Radar and Hydrology: Prefacementioning
confidence: 99%